DLR analysis on the noise emission from the RACER configuration - Yin, J.; Schwarz, T.; Wentrup, M.; Guntzer, F. (My University, 2019)
To answer the challenge of increasing range and speed of a rotorcraft, RACER (Rapid And Cost-Effective Rotorcraft) is developed by Airbus Helicopters. The RACER configuration incorporates an innovative “box-wing” design to provide lift and “pusher” propellers at the wing tips to generate thrust in forward flight. The noise sources from RACER do not only include conventional helicopter main rotor noise, but also propeller noise which can be significantly affected by interferences with the main rotor, wings and other parts of the configuration. Having been widely applied to the simulations of rotor and propellers, the DLR free wake code UPM and the aeroacoustic analysis tool APSIM are used for a detailed analysis and an improved understanding of the complex aerodynamics and aeroacoustics of the RACER configuration. The noise generation mechanisms of the various interactions among the propeller, the wings and the rotor as well as a variation in the sense of rotation of the propeller are numerically studied to allow finding mitigation means to reduce the interactions in the final RACER configuration. The noise from rotor and propeller emitted by the complete RACER configuration for various flight conditions is analyzed and the analysis of acoustic scattering of propeller noise by the RACER configuration is conducted.